The role of the job description as a corner in crime: Comparative analysis study - Aoumid Saeed Khudhur; Saman Abdulla Aziz (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The research topic is based on the role of the functional characteristic in criminal law as an assumed pillar in the crime, and the legislator regulated it through the two cases: The first case: The perpetrator is an employee or entrusted with a public service in some crimes such as the crime of bribery and the crime of arresting people in contravention of the law ... etc. The Iraqi legislator considered the perpetrator’s status an assumed pillar in the crime, and without it the crime would not be achieved with this description, provided that he uses his functional powers to carry out the crime, or that they exploit his position in committing the crime. The second case: the victim being an employee or entrusted with a public service in some other crime, such as the offense of insulting or threatening employees or those charged with a public service ... etc. The Iraqi legislator has considered the victim status a special element in thecrime, and without it the crime will not be realized, provided that the assault occurs while performing the job or because of it, and this is in order to provide the necessary protection for him to perform the duties of the job without fear.